Women and print culture in post-independence Buenos Aires - Macintyre, Iona (Colección Támesis. Monografías, 2010)
The woman question was a subject of discussion in post-independence Buenos Aires, reflected in the press and in the book world where writers contemplated the nature, role and status of women, linking the subjects to topics such as political transition, reform, modernisation, regional conflict and patriotic culture. This examination of a varied body of works dating from the 1820s, consisting of pamphlets, a history book, conduct literature and periodical literature, demonstrates the impact on these discussions of transatlantic print networks such as the book trade, and translations from Britain, France, and Spain.